The Fetal Basis of Amyloidogenesis: Exposure to Lead and Latent Overexpression of Amyloid Precursor Protein and β-Amyloid in the Aging Brain - Basha, M. Riyaz (J Neurosci, 2005)
The fetal basis of adult disease (FeBAD) hypothesis states that many adult diseases have a fetal origin. According to FeBAD, injury or environmental influences occurring at critical periods of organ development could result in “programmatic” changes via alterations in gene expression or gene imprinting that may result in functional deficits that become apparent later in life. Alzheimer's disease (AD) is a progressive neurodegenerative disorder that is characterized by excessive deposits of aggregated β-amyloid (Aβ) peptides, which are snippets of the β-amyloid precursor protein (APP). The predominately sporadic nature of AD suggests that the environment must play a role in neurodegeneration. To examine latent responses to an environmental agent, we exposed rodents to lead and monitored the lifetime expression of the APP gene. We observed that APP mRNA expression was transiently induced in neonates, but exhibited a delayed overexpression 20 months after exposure to Pb had ceased. This upregulation in APP mRNA expression was commensurate with a rise in activity of the transcription factor Sp1, one of the regulators of the APP gene. Furthermore, the increase in APP gene expression in old age was accompanied by an elevation in APP and its amyloidogenic Aβ product. In contrast, APP expression, Sp1 activity, as well as APP and Aβ protein levels were unresponsive to Pb exposure during old age. These data suggested that environmental influences occurring during brain development predetermined the expression and regulation of APP later in life, potentially altering the course of amyloidogenesis.